The digital immunization system of the future: imagining a patient-centric, interoperable immunization information system - Katherine M. Atkinson; Salima Saleem Mithani; Cameron Bell; Taylor Rubens-Augustson; Kumanan Wilson (SAGE Publishing, 2020)
To ensure the effectiveness of increasingly complex immunization programs in upper-middle and high-income settings, comprehensive information systems are needed to track immunization uptake at individual and population levels. The maturity of cloud systems and mobile technologies has created new possibilities for immunization information systems. In this paper, we describe a vision for the next generation of digital immunization information systems for upper-middle and high-income settings based on our experience in Canada. These systems center on the premise that the public is engaged and informed about the immunization process beyond their interaction with primary care, and that they will be a contributor and auditor of immunization data. The digital immunization system of the future will facilitate reporting of adverse events following immunization, issue digital immunization receipts, permit identification of areas of need and allow for delivery of interventions targeting these areas. Through features like immunization reminders and targeted immunization promotion campaigns, the system will reduce many of the known barriers that influence immunization rates. In light of the global COVID-19 pandemic, adaptive digital public health information systems will be required to guide the rollout and post-market surveillance of the SARS-CoV-2 vaccine.